Effects of acute moderate altitude exposure on physiological and technical performance in front crawl swimming - Mercade, J. J.; Arellano, R.; Feriche, B. (Biomechanics and Medicine in Swimming X, 2006)
The aim of this study was to analyse how acute moderate altitude exposure affects technique during a sub-maximal swimming protocol. Eleven subjects swam two steady-state test of 400 m front crawl, under normoxia (N, 690 m) and acute hypoxia (H, 2320 m). Stroke rate (SR) and stroke length (SL)' was recorded during each lap. Blood lactate concentration (BLa), heart rate (HR) and rating of perceived exertion (RPE) t were also measured after each trial. Results showed a reduction in SL with an increase in SR by altitude effect (p<0.05). HR, BLa and RPE were increased during altitude test respect normoxia (p<0.05). The obtained results did not show relation between physiological and technical variables in N and H. Technical parameters, like physiological ones, should be considered in altitude training camps.